Evidence for Immune Response, Axonal Dysfunction and Reduced Endocytosis in the Substantia Nigra in Early Stage Parkinson’s Disease - Dijkstra, Anke A.; Ingrassia, Angela; de Menezes, Renee X.; van Kesteren, Ronald E.; Rozemuller, Annemieke J. M.; Heutink, Peter; van de Berg, Wilma D. J. (PloS one, 2015)
Subjects with incidental Lewy body disease (iLBD) may represent the premotor stage of Parkinson's disease (PD). To elucidate molecular mechanisms underlying neuronal dysfunction and alpha-synuclein pathology in the premotor phase of PD, we investigated the transcriptome of the substantia nigra (SN) of well-characterized iLBD, PD donors and age-matched controls with Braak alpha-synuclein stage ranging from 0-6. In Braak alpha-synuclein stages 1 and 2, we observed deregulation of pathways linked to axonal degeneration, immune response and endocytosis, including axonal guidance signaling, mTOR signaling, EIF2 signaling and clathrin-mediated endocytosis in the SN. In Braak stages 3 and 4, we observed deregulation of pathways involved in protein translation and cell survival, including mTOR and EIF2 signaling. In Braak stages 5 and 6, we observed deregulation of dopaminergic signaling, axonal guidance signaling and thrombin signaling. Throughout the progression of PD pathology, we observed a deregulation of mTOR, EIF2 and regulation of eIF4 and p70S6K signaling in the SN. Our results indicate that molecular mechanisms related to axonal dysfunction, endocytosis and immune response are an early event in PD pathology, whereas mTOR and EIF2 signaling are impaired throughout disease progression. These pathways may hold the key to altering the disease progression in PD.